Comportamento bioquímico e fisiológico de sementes florestais nativas durante a embebição - Borges, Eduardo Euclydes de Lima e (2003)
This work aimed to study the biochemical and physiological changes, with emphasis on alpha-galactosidase enzyme, which occur during the germination of Platymiscium pubescens, Tachigalia multijuga and Caesalpinia peltophoroides seeds submitted to different treatments. Platymiscium pubescens seeds were osmoconditioned in polyethilenoglycol (PEG, m.w. 6,000) and the alterations in water content, embryonic axis growth, germination, cellular wall, protein carbohydrate mobilization and alpha-galactosidase were analyzed. Moisture of seeds maintained in water stabilized after the moisture of those maintained in PEG. The germination of water-maintained seeds, which were regarded as control, reached 30% in 120 h. While the fresh mass and embryonic axis length increased significantly during permanence in the PEG solution, fresh mass did not alter significantly. Arabinose was found to be the main constituent of the membrane surrounding the embryo and, together with xylose, showed significant decreases during permanence in the PEG solution. Alpha-galactosidase activity underwent significant changes during the 120 h period in the PEG solution. Rhamnose, arabinose and xylose contents altered significantly in the pectic fraction, while rhamnose was the only one found in the hemicellulosic fraction of the embryonic axis wall. Glucose contents reduced significantly both in the embryonic axis and in the cotyledons during osmocondioning. Stachyose and raffinose contents had no significant alterations in the cotyledons while sucrose content reduced significantly. Protein contents decreased significantly during the 120h osmoconditioning. It was concluded that osmoconditioning potentialized seed germination during the imbibing process, resulting in cellular wall changes due to the deposition of reducing sugars. In view of the significant alterations observed in alpha-galactosidase activity in P. pubescens seeds during osmoconditioning and its likely involvement in the germination process, this work was developed to characterize the enzyme in the embryo and in the cotyledons of seeds of this species. The seeds were placed to imbibe in water and samples withdrawn for biochemical and kinetic characterization in the embryonic axis and cotyledons. While the specific activity in the axis increased during 96 h, cotyledon activity showed a small increase. Alpha-galactosidase activity in the axis was maximal during the pH interval from 4.5 to 6.0 and cotyledon activity at 6.0. The 55 oC temperature stimulated enzyme activity the most in both compartments. The thermo-stabilities of the axis and cotyledon enzymes were maintained for 1,500 h at 40 oC. The Alpha-galactosidase activity in the embryonic axis was inhibited by melibiosis, CuSO4 and SDS whereas that of the cotyledons was inhibited by all the effectors. KM values for the embryo and cotyledons were 3.37 and 0.26 mM, respectively, showing that the alphagalactosidases are different and have activities at different times during imbibition. Similarly, the alpha-galactosidase of the embryo and cotyledons of Caesalpinia peltophoroides seeds was characterized, aiming to establish the relationship between its activity and the alterations in the cellular wall of the micropyle in the seeds. During the 114 h imbibition, samples were withdrawn for quantification of alpha-galactosidase activity, protein and sugars. Germination took place after 96 h imbibition, without any changes occurring in the cellular wall of the micropyle, where a greater proportion of arabinose, with a tendency to increase during imbibition, was observed. Enzyme activity was detected in dry seeds, in the embryonic axis and in the cotyledons, increasing in the first after 24 h imbibition. Protein content decreased continuously in the embryonic axis, after 24 h imbibition, while maintaining itself stable in the cotyledons. Alpha- galactosidase activity was maximal at temperatures of 55 oC for the embryonic axis and 50 oC for the cotyledons. The pH that stimulated enzyme activity the most was in the range of 5.5 - 6.0 for the embryonic axis and 4.5 - 5.0 for the cotyledons. Melibiosis, CuSO4, SDS and galactose inhibited the alphagalactosidases of the embryonic axis and cotyledons. On the other hand, mercaptoethanol stimulated the activity of the cotyledons. Thermo stability was also shown to be high at the temperature of 50 oC. The KM for the substrate r - NPGal for the alpha-galactosidase of the embryo and cotyledons was 1.74 and 2.64, respectively. The alpha-galactosidases of the two species were also found to be different from each other, with specificities and distinct behaviors characteristic of the ecotype of each species. Aiming to study the effect of the pre-germinating treatments on the activities of the enzymes alpha-galactosidase and beta-mannanase, in the imbibition percentage, germination percentage and velocity, protein synthesis and alteration of the membrane surrounding the embryo in seeds of Tachigalia multijuga, seeds of three selected trees were collected and sulphuric acid, snipped of seeds testa at micropyle end or at the other end and boiling water treatments were applied. No seed germination occurred in the boiling water treatment. Except for the sulphuric acid for 10 min, all the other treatments resulted in germination percentage greater than the control. On the other hand, germination velocity in the various treatments was different from that of the control only in one of the trees. Seeds water percentage of the ones treated in acid for 20 min. and boiling water for 60 sec differed statistically from the control. The enzyme activities and protein contents during imbibition were statistically different between the water and acid treatments. While the alpha-galactosidase remained constant in the boiling water treatment, during imbibition, those in the sulphuric acid increased during the 96 h period, followed by a decrease. In contrast, beta-mannanase activity was not detected after 96 h. in the hot water treatment, increasing significantly in the sulphuric acid treatment. It was verified that, overall, the contents of all the sugar components of the seed teguments in the control, were significantly lower than those in the two pre-germinating treatments, especially during 144 h imbibition. It was concluded that there is no relation between the activity of either enzyme and the alterations in the seed teguments, with the likelihood of both enzymes acting on mobilization of reserves rather than on the weakening of the tegument in the pre-germinating phase.